Influence Of Self-Leadership And Entrepreneurial Orientation Toward Performance Mediated By Organizational Commitment On Sme’s - Nurul QOMARI; Anwar SANUSI; Fajar SUPANTO (International Journal of Environmental, Sustainability, and Social Science, 2021)
This study aims to analyze and explain the effect of Self-Leadership, and Entrepreneurial Orientation on Organizational Commitment. Simultaneously, the paper analyzes the effect of Self-Leadership and Entrepreneurial Orientation on Performance. Secondly, to the influence of Organizational Commitment as well as Self-Leadership and Entrepreneurial Orientation on Performance. The number of samples in this study were 153 consist of small and medium enterprises. Structural Equation Modeling (SEM) were used in this study. The results showed that Self-Leadership and Entrepreneurial Orientation influence Organizational Commitment. Self-Leadership and Entrepreneurial Orientation affect Performance. Organizational Commitment influences Performance. Self-Leadership and Entrepreneurial Orientation influence Performance through Organizational Commitment.